Analysis Of Problem Solving Ability Mathematical Students Assisted With Animation Video Media - Hesti, Siska; Sina, Ibnu; Wahyuningsih, Eleonora Dwi (Integral (Jurnal Penelitian Pendidikan Matematika), 2023)
This study aims to describe student’s mathematical problem solving abilities assisted by animated video media. This type of research is a qualitative descriptive research. The learning media used is Canva-based animated video media. The research subjects were class VII F students of SMP Negeri 3 Brebes Semester II for the 2022/2023 academic year. Subjects were taken using random sampling from written essay test scores for 6 subjects, namely 2 subjects with high mathematical problem solving abilities, 2 subjects with moderate mathematical problem solving abilities, and 2 subjects with low mathematical problem solving abilities. Data collection techniques in this study used tests, interviews, and documentation. According to Polya, the indicators of mathematical problem-solving ability are (1)understanding the problem, (2)devising a plan, (3)carrying out the plan, and (4)looking back. Based on the results of the study showed that: high problem-solving ability fulfill 4 indicators of mathematical problem-solving ability there are understanding the problem, devising a plan, carrying out the plan, and looking back. Moderate problem-solving ability fulfill 3 indicators of mathematical problem-solving ability there are understanding the problem, carrying out the plan, and looking back or there are understanding the problem, carrying out the plan, and looking back. Low problem-solving ability fulfill 1 indicator of mathematical problem-solving ability there is understanding the problem,or does not fulfill all indicators.